2012
DOI: 10.1371/journal.pone.0037296
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative 3D Motility Analysis of Trypanosoma brucei by Use of Digital In-line Holographic Microscopy

Abstract: We present a quantitative 3D analysis of the motility of the blood parasite Trypanosoma brucei. Digital in-line holographic microscopy has been used to track single cells with high temporal and spatial accuracy to obtain quantitative data on their behavior. Comparing bloodstream form and insect form trypanosomes as well as mutant and wildtype cells under varying external conditions we were able to derive a general two-state-run-and-tumble-model for trypanosome motility. Differences in the motility of distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…brucei typically contain cells with a variety of different swimming behaviours varying from persistent directional swimming to tumbling [56, 57]. Cell microenvironment affects this motility, whereby trypanosomes cultured in the low viscosities of tissue culture media predominantly tumble [54].…”
Section: Discussionmentioning
confidence: 99%
“…brucei typically contain cells with a variety of different swimming behaviours varying from persistent directional swimming to tumbling [56, 57]. Cell microenvironment affects this motility, whereby trypanosomes cultured in the low viscosities of tissue culture media predominantly tumble [54].…”
Section: Discussionmentioning
confidence: 99%
“…Digital in-line holographic microscopy (DIHM), as schematically shown in Fig. 3, is a technique capable to capture fast, three-dimensional motions by recording a movie of coherent far-field diffraction patterns of the sample volume [55][56][57][58][59]. A coherent laser beam is focused on a small pinhole to create a divergent light cone, which illuminates the volume of interest.…”
Section: Biofouling Research: the Quest For Environmentallymentioning
confidence: 99%
“…Early work by Walker () demonstrated that motility is driven by a tractile flagellar beat that initiates at the tip of the flagellum and travels to the flagellum base, the opposite of what is seen in most other eukaryotic flagella. More recent analyses of T. brucei motility using high‐speed, high‐resolution video microscopy provided adjustments to the original ‘auger‐like’ description and further emphasized that parasite motility is a prominent feature of these pathogens in the blood (Rodriguez et al ., ; Uppaluri et al ., ; Heddergott et al ., ; Weisse et al ., ).…”
Section: Introductionmentioning
confidence: 97%